Psychomotor Car-Driving Abilities after Robotically Assisted Totally Endoscopic Coronary Artery Bypass Grafting - Kopp, Martin; Knuenz, Angelika; Oberascher, Franziska; Pfaffenberger, Nicole; Lucic, Nicole; Ruedl, Gerhard; Holzner, Bernhard; Bonaros, Nikolaos; Johannes, Bonatti (The Thoracic and Cardiovascular Surgeon, 2012)
Objective Postoperative cognitive decline is a common complication after coronary artery bypass graft surgery. As robotically assisted totally endoscopic coronary artery bypass grafting (TECAB) has shown several positive impacts on recovery and quality of life, the aim of this study was to assess psychomotor functioning relevant for car-driving abilities before and after this intervention.Methods A total of 20 patients who underwent TECAB completed a neuropsychological test battery including conventional and computerized assessments [Trail Making Test (TMT A + B), Leeds Psychomotor Tester (LPT), Test System for Attentional Performance (TAP 2.1)] before surgery (T0) and 1 week (T1) and 3 months (T2) after surgery.Results Data show no significant cognitive decline between T0, T1, and T2 following TECAB. Significant improvements were measured from T0 to T2 for psychomotoric function and visual attention (TMT A; p = 0.038) and for reaction time, which was significantly shorter after 3 months in comparison with T0 and T1; p = 0.001).Conclusion Data of our preliminary study show no relevant cognitive decline caused from TECAB and therefore do not contradict the practice of early car driving after this procedure.
Keywords: coronary artery bypass crafting; minimally invasive cardiac surgery; cognitive functioning; driving ability